Caloric restriction and redox state: Does this diet increase or decrease oxidant production? - Kowaltowski, Alicia J (Redox Rep, 2013)
Calorie restriction (CR) is well established to enhance the lifespan of a wide variety of organisms, although the mechanisms are still being uncovered. Recently, some authors have suggested that CR acts through hormesis, enhancing the production of reactive oxygen species (ROS), activating stress response pathways, and increasing lifespan. Here, we review the literature on the effects of CR and redox state. We find that there is no evidence in rodent models of CR that an increase in ROS production occurs. Furthermore, results in Caenorhabditis elegans and Saccharomyces cerevisiae suggesting that CR increases intracellular ROS are questionable, and probably cannot be resolved until adequate, artifact free, tools for real-time, quantitative, and selective measurements of intracellular ROS are developed. Overall, the largest body of work indicates that CR improves redox state, although it seems improbable that a global improvement in redox state is the mechanism through which CR enhances lifespan.